Gay and Bisexual Men’s Perceptions of HIV Risk in Various Relationships - Shaver, John (Am J Mens Health, 2018)
Men who have sex with men (MSM) bear a disproportionate burden of HIV incidence in the United States. Previous study of sexual decision-making and HIV risk among MSM has not accounted for relationship dynamics. Further research must examine this connection between relationship dynamics and sexual decision-making, especially regarding condomless anal intercourse. This study analyzes data gathered from gay and bisexual men regarding their sexual partners and sexual decision-making over a 10-week period through personal relationship diaries (PRDs) and a follow-up in-depth interview (IDI). Through coding and extraction of relationship dynamics, key patterns of participants’ sexual decision-making processes were examined based on relationship type, which was categorized by commitment, formality, and sexual agreement. Participants’ sexual relationships can be divided into five categories: (a) Uncommitted, one time, (b) Uncommitted, ongoing, (c) Transitioning or unknown commitment, (d) Committed, nonmonogamous, and (e) Committed, monogamous. These five categories correspond to patterns in sexual decision making and consequent sexual risk-taking behaviors. Each of these influence HIV risk within male–male sexual encounters in a particular manner, and understanding these is important for appropriately tailored HIV prevention interventions for MSM. Recommendations are included for interventions seeking to address HIV risk across a wide variety of MSM sexual relationships.